2020
DOI: 10.1038/s41467-020-18629-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional genetic encoding of sulfotyrosine in mammalian cells

Abstract: Protein tyrosine O-sulfation (PTS) plays a crucial role in extracellular biomolecular interactions that dictate various cellular processes. It also involves in the development of many human diseases. Regardless of recent progress, our current understanding of PTS is still in its infancy. To promote and facilitate relevant studies, a generally applicable method is needed to enable efficient expression of sulfoproteins with defined sulfation sites in live mammalian cells. Here we report the engineering, in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…1b). 17 The selection was conducted in Saccharomyces cerevisiae by following a previously established procedure. [18][19][20] Briefly, the selection was based on the expression of plasmid pGADGAL4-encoded transcriptional activator GAL4, in which codons of Thr44 and Arg110 are replaced with amber codons (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). 17 The selection was conducted in Saccharomyces cerevisiae by following a previously established procedure. [18][19][20] Briefly, the selection was based on the expression of plasmid pGADGAL4-encoded transcriptional activator GAL4, in which codons of Thr44 and Arg110 are replaced with amber codons (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The evolved CMFRS shares two common mutations, L71V and D182G, with a sTyrRS that we reported previously for the encoding of sulfotyrosine 10 (sTyr) in mammalian cells. 17 Analysis of the crystal structure of sTyrRS in complex with its substrate (PDB ID: 6WN2) have shown that both mutations expand the active site in order to accommodate the large substituent at the para-position of Tyr. In addition, the D182G mutation eliminates the electrostatic repulsion between the negatively charged Asp and the substituent on Tyr.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from various chemical and semisynthetic methods, [2–5] genetically encoding noncanonical amino acids (ncAAs) using orthogonal tRNA‐synthetase pairs in live cells [6,7] has been extensively employed to introduce various PTMs and mimetics into proteins. Representative examples include glycosylation, [8,9] phosphorylation, [10–12] alkylation or acylation, [13,14–19] sulfation, [20–22] and so on. Knockout of release factor further allows the simultaneous incorporation of PTM‐bearing ncAAs at multiple sites into proteins [23] …”
Section: Figurementioning
confidence: 99%
“…Di‐deuterium‐labeled sTyr (sTyr‐D2) is recommended because the sulfoester bond in sTyr is labile and can readily decompose to yield Tyr under mass spectrometry conditions. Purified eGFP 40sTyr was subjected to trypsin digest followed by analysis with a time of flight (Q‐TOF) hybrid mass spectrometer (He et al., 2020). No significant mis‐incorporation of natural amino acids was detected when 1 mM sTyr was added in cell culture medium.…”
Section: Commentarymentioning
confidence: 99%
“…(B) Flow cytometry analysis of HEK293T cells co-transfected with psTyrRS and pEGFP in the absence and presence of sTyr (1 mM). The normalized fluorescence was calculated by multiplying the mean fluorescence intensity by the percentage of fluorescent cells(He et al, 2020).He et al…”
mentioning
confidence: 99%